Simulation on billet extrusion for PMMA birefringent microstructured optical fiber preforms - Fung, Yuan Zhao (2018)
Plastic Optical Fiber or also known as Polymer Optical Fiber (POF) has been an object of interest in the recent years. It is a cheaper alternative and more user-friendly as compared to glass optical fiber. However, it suffers more attenuation and losses, and hence, more often used in short distance transmissions. Currently, majority of the commercial POF are made of PMMA material. By improving the manufacturing process, the cost and quality of PMMA POF can be improved.